Poly(methyl acrylate) plus Mesoporous Silica Nanohybrids : Mechanical and Thermophysical Properties (2007)
ABSTRACT: A mesoporous silica MCM-48 is used as a reinforcement agent for poly(methyl acrylate) (PMA). Methyl acrylate is introduced into the mesoporous silica that has an interconnected porous structure, allowing monomer diffusion into the pores before the polymerization reaction. In order to improve the silica plus polymer adhesion and to decrease the silica agglomeration, the silanol groups of the silica are functionalized with methyl groups without decreasing significantly the pore size. The silica is characterized by nitrogen adsorption, scanning electronic microscopy (SEM) and infrared (IR) spectroscopy. The nanohybrids so obtained are analyzed by tensile testing, thermogravimetry (TGA), differential scanning calorimetry (DSC) and dynamical mechanical analysis (DMA). The highest improvement of mechanical and thermophysical properties is achieved for nanohybrids containing 5 wt. % mesoporous silica. At 10 % silica, agglomeration of the filler takes place and the dispersed phase is less effective in reinforcing the polymer matrix.